THE ATYPICAL SITE OF URETERAL METASTASIS IN A PATIENT WITH CASTRATION-REFRACTORY PROSTATE CANCER. A CLINICAL CASE AND A REVIEW OF LITERATURE - B. Ya. Alekseev (Onkourologiâ, 2014)
Prostate cancer (PC) is one of the most burning problems of modern urologic oncology because the incidence of this pathology remains high now. Castration-refractory PC (CRPC) is an extremely heterogeneous disease whose prognosis is largely determined by a number of factors, including the number and site of distant metastases. In the patients with CRPC, distant metastases are verified with the highest frequency in the bones, lymph nodes, and lung. Atypical metastatic involvement cases are rarely observed in patients with CRPC. The paper gives a review of literature and describes a clinical case of the atypical site of metastasis in a patient with CRPC.